IMPLEMENTASI PERDA AGAM NO. 10 DI NAGARI BALINGKA: PENDEKATAN SIYASAH QUR'ANIYAH - Nabila Fitri Gunawan; Muhammad Taufiq (Adisam Publisher, 2025)
This study evaluates the implementation of Agam Regency Regional Regulation Number 10 of 2017 concerning waste management in Nagari Balingka, by applying the Siyasah Qur’aniyah approach, namely governance based on Islamic principles. This study was conducted using a descriptive-analytical method through field observations, interviews, and documentation analysis. The results of the study indicate that the implementation of the Regional Regulation faces major challenges, such as low community participation, limited infrastructure, and lack of socialization related to waste management. The Siyasah Qur’aniyah approach, which emphasizes collaboration and the value of cleanliness as part of faith, is identified as a potential solution to overcome this problem. Research recommendations include increasing socialization, developing environmental education programs based on Islamic values, building adequate facilities, and providing incentives to increase community participation. The implementation of these steps is expected to strengthen a sustainable waste management system that is in accordance with religious teachings, creating a clean and healthy environment.